Succession as the Principle of Formation of Readiness of Teachers of Primary School to Work With Gifted Pupils in the System of Continuous Education - Ushmarova, Viktoriia (Pedagogical Discourse, 2015)
The main aspects of the phenomenon of succession within the philosophical, cultural, sociological, psychological and pedagogical sciences have been discussed in the article. As a result of scientific research it has been found that in the context of continuous education researchers distinguish several levels: the first level – the succession as a methodological regularity of development of individual in the system of continuous education; the second level - the succession as general and pedagogical principle on the basis of which the integral pedagogical process operates in system of continuous education; the third level – the succession as a didactic principle, which, together with other didactic principles provides an integral perception of courses of study; the fourth level – the succession as a single methodological principle of teaching. The essence of the principle of the succession as a methodological principle of investigation of the problem of formation of readiness of primary school teachers to work with gifted pupils in conditions of continuous pedagogical education has been determined. It was proved that succession is ensured on the basis of coordination and relationship of goals, content, methods of forming of readiness of primary school teachers to work with gifted pupils in pedagogical universities and postgraduate pedagogical institutions and according to the following conditions: taking into account the existing level of readiness to work with gifted and its consistent promotion, support to experience the integral nature of the process of formation of readiness to work with gifted pupils.